2019
DOI: 10.1152/ajpgi.00212.2018
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of histamine H1- and H2-receptor signaling pathways in inflammation-associated colonic tumorigenesis

Abstract: Inflammatory bowel disease (IBD) is a well-known risk factor for the development of colorectal cancer. Prior studies have demonstrated that microbial histamine can ameliorate intestinal inflammation in mice. We tested the hypothesis whether microbe-derived luminal histamine suppresses inflammation-associated colon cancer in Apcmin/+ mice. Mice were colonized with the human-derived Lactobacillus reuteri. Chronic inflammation was induced by repeated cycles of low-dose dextran sulfate sodium (DSS). Mice that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 71 publications
3
30
0
Order By: Relevance
“…It is also possible downstream signaling by specific histamine receptors functions through different proteins and pathways. For example, a recent study in colorectal cancer cells demonstrated that H2R activation reduced MAPK phosphorylation to suppress their activities [44], which differs from the activating effects of other histamine receptors on MAPK pathways [44,45]. Our findings here demonstrate that the MAPK and PI3K/Akt signaling pathways are involved in the histamine-mediated promotion of KSHV lytic reactivation.…”
Section: Discussionsupporting
confidence: 45%
“…It is also possible downstream signaling by specific histamine receptors functions through different proteins and pathways. For example, a recent study in colorectal cancer cells demonstrated that H2R activation reduced MAPK phosphorylation to suppress their activities [44], which differs from the activating effects of other histamine receptors on MAPK pathways [44,45]. Our findings here demonstrate that the MAPK and PI3K/Akt signaling pathways are involved in the histamine-mediated promotion of KSHV lytic reactivation.…”
Section: Discussionsupporting
confidence: 45%
“…HRH1 is a member of histamine receptor family, and it has been reported that inhibition of HRH1 could not only enhance antitumor therapeutic response in breast cancer, 45 but also suppress colonic tumorigenesis. 46 These evidences indicate that HRH1 may also be a potential target in IRS-high PTC patients.…”
Section: Discussionmentioning
confidence: 95%
“…Activation of H 1 R elicits physiological processes that include modulation of circadian rhythms [ 4 ], responses to allergens, and proinflammatory cytokine production [ 5 ]. H 1 R stimulation has also been implicated in inflammation-associated tumorigenesis [ 6 ]. H 1 R activation by endogenous histamine is blocked by widely recognized drugs known as antihistamines to prevent or reduce allergic responses.…”
Section: Introductionmentioning
confidence: 99%